Abdominal, thoracic, and cardiac point-of-care ultrasound skills following an in-person hands-on training course for early-track emergency clinicians - Guillaumin, Julien; Cavanagh, Amanda; Rechy, Jaime; Callahan, Morgan; Hanel, Rita (Frontiers in Veterinary Science, 2025)
IntroductionThis study was designed to assess baseline compared to three months procedural skills performing abdominal, thoracic, and cardiac point-of-care ultrasound (POCUS) after POCUS training.MethodsA POCUS training was designed as a 3-hour online course, followed by a 2-day in-person course consisting of 3.5 hours of case-based lectures and 4 hours of hands-on laboratory on anesthetized dogs each day. In-person procedural assessment was performed using an anesthetized dog and consisted of identifying 22 anatomical structures in 6 minutes. The assessment was performed pre-course and repeated three months post-course in an identical environment.ResultsFifty-six veterinarians from the Veterinary Emergency Group New ER Doctor program were enrolled. Participants identified an overall 7.8 ± 2.6 structures in the pre-course assessment, compared to 13.8 ± 5.9 in the post-course assessment (p < 0.0001). For abdominal POCUS, participants identified 5.9 ± 1.9 structures out of 12 in the pre-course and 9.0±1.5 in the post-course assessment (p < 0.0001). For thoracic POCUS, participants identified 1.7 ± 1.2 structures out of 4 in the pre-course and 3.4±0.7 in the post-course assessment (p < 0.0001). For cardiac POCUS, participants identified 0.07 ± 0.3 structures out of 6 pre and 1.5±1.6 post-course assessment (p < 0.0001). There was no impact of pre-course tested variables on the pre-course score. Survey-based course satisfaction was 100%.DiscussionThe Veterinary Emergency Group New ER Doctor POCUS course improved participants’ ability to correctly identify anatomical structures on POCUS when assessed three months after the course.